A Multicentered Study on Epidemiologic and Clinical Characteristics of 37 Neonates With Community-acquired COVID-19 - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2020)
Background: Coronavirus disease 2019 (COVID-19) primarily affects adults and spares children, whereas very little is known about neonates. We tried to define the clinical characteristics, risk factors, laboratory, and imagining results of neonates with community-acquired COVID-19. Methods: This prospective multicentered cohort study included 24 neonatal intensive care units around Turkey, wherein outpatient neonates with COVID-19 were registered in an online national database. Full-term and premature neonates diagnosed with COVID-19 were included in the study, whether hospitalized or followed up as ambulatory patients. Neonates without severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) via reverse transcriptase-polymerase chain reaction testing or whose mothers had been diagnosed with COVID-19 during pregnancy were excluded. Results: Thirty-seven symptomatic neonates were included. The most frequent findings were fever, hypoxemia, and cough (49%, 41%, 27%, respectively). Oxygen administration (41%) and noninvasive ventilation (16%) were frequently required; however, mechanical ventilation (3%) was rarely needed. Median hospitalization was 11 days (1-35 days). One patient with Down syndrome and congenital cardiovascular disorders died in the study period. C-reactive protein (CRP) and prothrombin time (PT) levels were found to be higher in patients who needed supplemental oxygen (0.9 [0.1-8.6] vs. 5.8 [0.3-69.2]p= 0.002, 11.9 [10.1-17.2] vs. 15.2 [11.7-18.0]p= 0.01, respectively) or who were severe/critical (1.0 [0.01-8.6] vs. 4.5 [0.1-69.2]p= 0.01, 11.7 [10.1-13.9] vs. 15.0 [11.7-18.0]p= 0.001, respectively). Conclusions: Symptomatic neonates with COVID-19 had high rates of respiratory support requirements. High CRP levels or a greater PT should alert the physician to more severe disease.
Keywords: coronavirus infections; SARS-CoV-2; COVID-19; newborn; acute respiratory distress syndrome; ACE2; SARS